2003
DOI: 10.1017/s1041610203008858
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Psychotic Symptoms and Dependence in Activities of Daily Living Among Older Adults With Alzheimer's Disease

Abstract: Background: Alzheimer's disease (AD) is associated with dependence in activities of daily living (ADL). In addition to the cognitive impairment resulting from AD, the presence of psychotic symptoms may further increase this dependence. The objective of this study was to quantify the additional contribution of psychotic symptoms to dependence in ADL. Method: We analyzed data from 558 individuals with AD referred to a memory clinic. Information on ADL, psychotic symptoms, depression symptoms, and cognition was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Our AD patients were in a mild stage, but a previous study found a relationship between motor disability and everyday functioning in severely affected AD patients [40]. Consistent with several previous studies [3, 4, 9], behavioral disturbance was the best predictor of physical ADL for patients with AD. This may reflect a lack of motivation (i.e., apathy) or focus (i.e., disinhibition) necessary to carry out a task.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our AD patients were in a mild stage, but a previous study found a relationship between motor disability and everyday functioning in severely affected AD patients [40]. Consistent with several previous studies [3, 4, 9], behavioral disturbance was the best predictor of physical ADL for patients with AD. This may reflect a lack of motivation (i.e., apathy) or focus (i.e., disinhibition) necessary to carry out a task.…”
Section: Discussionsupporting
confidence: 84%
“…Cognitive decline in AD is often accompanied by behavioral changes such as depression, apathy, agitation or disinhibition [1], and in some combination these factors lead to profound functional decline with a gradual loss of independence in performing usual activities of daily living (ADL)[2]. Although cognitive impairment is usually viewed as the primary determinant of functional decline in AD, several studies have linked behavioral deficits to disability in physical self-maintenance (bathing, toileting, eating) and instrumental (e.g., financial management, shopping) ADL [3, 4] and particularly rapid loss of functional independence [39]. In some cases, the relationship between behavioral deficits and ADL decline is independent of cognitive dysfunction [6, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deterioration in these activities is a common complaint of both patients and their families and is usually associated with their distress. As decreases in functional performance may contribute to the patient's overall disability (Tran et al, 2003) and impair personal autonomy, it is important to identify the factors that compromise functional competency.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relation of the PFDs as assessed by the NPI to the hallmarks of psychogeriatric patients -the cognitive function disorders and the related handicaps in activities of daily living (ADL) -is not obvious [Aalten et al, 2004;Tran et al, 2003]. The same implies to relevant general details such as gender, age, marital status, domicile and type of primary caregiver.…”
Section: Introductionmentioning
confidence: 99%